2010
DOI: 10.1016/j.juro.2010.03.063
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish Reflux Trial in Children: V. Bladder Dysfunction

Abstract: After toilet training a third of these children with dilating reflux had lower urinary tract dysfunction, mainly voiding phase problems. Dysfunction was associated with persistent reflux and renal damage while dysfunction at study entry did not predict the 2-year outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(48 citation statements)
references
References 21 publications
3
37
1
6
Order By: Relevance
“…Other host factors could include dysfunctional bladder emptying [4], detrusor instability [5], constipation, and fecal soiling.…”
Section: Etiology/physiopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Other host factors could include dysfunctional bladder emptying [4], detrusor instability [5], constipation, and fecal soiling.…”
Section: Etiology/physiopathologymentioning
confidence: 99%
“…(4) The usefulness of a full imaging work-up after a first fUTI is questioned. The new guidelines suggest less aggressive imaging strategies, to reduce radiation exposure and costs.…”
mentioning
confidence: 99%
“…Relevant epidemiological studies allow for the supposition that the prevalence of LUTD in children is variable, possibly affecting between 2% and 25% of the population [3][4][5][6][7][8][9][10][11][12]. Despite this disparity in the prevalence reported in studies, in which the informants are generally the parents, LUTD is common in the pediatric population and represents a challenge for specialized interdisciplinary teams.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the Swedish Reflux Trial in Children, a subgroup analysis of LUTD in terms of prevalence, VUR resolution rates, UTI recurrence, and development of renal damage was performed. 35 The authors found that LUTD was seen in 34% of children with VUR, and recurrent urinary tract infections were found in 33% versus 20% of children with and without LUTD, respectively. This study also observed a lower rate of VUR resolution (22% versus 56%), and a much higher rate of renal damage (85% versus 52%) among children with LUTD.…”
Section: Bladder/bowel Rehabilitationmentioning
confidence: 96%